2013
DOI: 10.1158/1535-7163.targ-13-b113
|View full text |Cite
|
Sign up to set email alerts
|

Abstract B113: GSK3A is redundant with GSK3B in modulating drug resistance and chemotherapy-induced necroptosis.

Abstract: Purpose of the study. GSK3A and GSK3B isoforms perform similar functions but they are not completely redundant, depending on the cell type, biological process and differentiative status (Rayasam GV et al, Br J Pharmacol, 2009). We recently demonstrated that GSK3B inhibition enables necroptosis in response to chemotherapy in drug-resistant colon carcinoma cells (Grassilli E et al, Clin Cancer Res, 2013). Here we investigated whether GSK3A is redundant with GSK3B in modulating drug resistance and chemotherapy-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In recent years, glycogen synthase kinase‐3 beta (GSK‐3β), a multifunctional serine/threonine kinase, has attracted significant attention for its regulation of innate inflammatory processes . GSK‐3β‐mediated inflammation has been linked to number of diseases, such as diabetes, heart disease, neurodegenerative diseases, and cancer . Many studies have demonstrated that GSK‐3β may be a potential treatment target of anti‐inflammatory drugs for use in the clinic .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, glycogen synthase kinase‐3 beta (GSK‐3β), a multifunctional serine/threonine kinase, has attracted significant attention for its regulation of innate inflammatory processes . GSK‐3β‐mediated inflammation has been linked to number of diseases, such as diabetes, heart disease, neurodegenerative diseases, and cancer . Many studies have demonstrated that GSK‐3β may be a potential treatment target of anti‐inflammatory drugs for use in the clinic .…”
Section: Introductionmentioning
confidence: 99%
“…7 GSK-3β-mediated inflammation has been linked to number of diseases, such as diabetes, 8 heart disease, 9 neurodegenerative diseases, 10 and cancer. 11 Many studies have demonstrated that GSK-3β may be a potential treatment target of anti-inflammatory drugs for use in the clinic. 12 For example, lithium chloride (LiCl), a GSK-3β inhibitor, is used to treat bipolar disorder and Alzheimer disease, 13 SB415286 is used to treat neuronal apoptosis, 14 and hymenialdisine is used to treat inflammation.…”
mentioning
confidence: 99%